2020
DOI: 10.1163/22119000-12340172
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Perspectives on Investment Arbitration: What Do We Know? Does It Matter?

Abstract: Due to the problem-centric nature of its mandate, empirical research has been relatively central in the United Nations Commission on International Trade Law (UNCITRAL) investment arbitration reform process. In this article, the authors seek to provide a state-of-the-art summary and assessment of empirical studies on the six identified concerns of states: legal cost, duration of proceedings, consistency, correctness, diversity and independence. The article asks: (1) What do we know? and (2) Does it matter? The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…International arbitration differs from local court proceedings Behn et al (2020). Its adaptability, the ability for disputing parties to choose arbitrators with specialised knowledge, and the global recognition and enforcement of arbitral rulings, as emphasised by international agreements like the New York Convention, set it apart.…”
Section: Literature Review 151 the Landscape Of Investment Dispute Re...mentioning
confidence: 99%
“…International arbitration differs from local court proceedings Behn et al (2020). Its adaptability, the ability for disputing parties to choose arbitrators with specialised knowledge, and the global recognition and enforcement of arbitral rulings, as emphasised by international agreements like the New York Convention, set it apart.…”
Section: Literature Review 151 the Landscape Of Investment Dispute Re...mentioning
confidence: 99%
“…Much concern has been raised, especially by States, as to hurdles they have encountered in the recoverability of costs (Behn et al , 2020, pp. 188–250).…”
Section: Provisions On Prevention Of Frivolous Claims In the European...mentioning
confidence: 99%
“…Among them, Vietnam only could get partial recovery in one case [44]. A large number of States have also raised the same concerns to hurdles they encountered in the recoverability of costs awards (Behn et al , 2020, pp. 188–250).…”
Section: Provisions On Prevention Of Frivolous Claims In the European...mentioning
confidence: 99%
“…Despite the predominantly positive trends, the diverse appointments have been growing at a sluggish rate and are driven disproportionately by arbitral institutions (Behn et al, 2020). Representatives of various arbitral institutions confirmed that the diversity of the tribunals is high on their respective agendas (QMUL-White and Case, 2021).…”
Section: Gender Diversitymentioning
confidence: 99%